Prevalence of sexually transmitted pathogens among women attending a methadone clinic in Israel. Issue 2 (April 1991) - Samra, Z; Dan, M; Segev, S; Fintsi, Y; Bar-Shany, S; Weinberg, M; Gutman, R
Abstract : OBJECTIVE–To assess the prevalence of sexually transmitted pathogens in drug-addicted women in Tel Aviv, Israel. DESIGN–A prospective study conducted between March and July 1987. SETTING–A methadone clinic in Tel Aviv, Israel. SUBJECTS–Sixty four asymptomatic female drug addicts were studied; 38 of them were declared practising prostitutes. METHODS–Cervical specimens were obtained for cultures, and blood samples were drawn for serological tests. Demographic data and sexual histories were obtained using a standard questionnaire. RESULTS–Chlamydia trachomatis was detected in the cervix of 25% of women; 98% had antibody titres (greater than 1:64). Mycoplasma hominis and Ureaplasma urealyticum were isolated in 57% and 65% respectively. Gardnerella vaginalis was detected in 17% of women, and herpes simplex virus was cultured from two prostitutes. Five per cent of women were carriers of HBsAg, while 57% had HBSs and/or HBc antibodies. Only one prostitute had specific treponemal antibodies. In no case were gonococci or group B streptococci isolated, and HIV serology was invariably negative. CONCLUSION–Chlamydia and genital mycoplasmas appear to be the prevailing pathogens in Israeli drug-addicted women, while gonococci and Treponema pallidum occur only rarely.